Anger at work - Porat, Roni; Levy Paluck, Elizabeth (Frontiers in Social Psychology, 2024)
What happens when you express anger at work? A large body of work suggests that workers who express anger are judged to be competent and high status, and as a result are rewarded with more status, power, and money. We revisit these claims in four pre-registered, well-powered experiments (N = 3,852), conducted in the US, using the same methods used in previous work. Our findings consistently run counter to the current consensus regarding anger's positive role in obtaining status and power in the workplace. We find that when men and women workers express anger they are sometimes viewed as powerful but they are consistently viewed as less competent. Importantly, we find that angry workers are penalized with lower status compared to workers expressing sadness or no emotions. We explore the reasons for these findings both experimentally and descriptively and find that anger connotes less competence and warmth and that anger expressions at work are perceived as inappropriate, an overreaction, and as a lack of self-control. Moreover, we find that people hold negative attitudes toward workplace anger expressions, citing them as relatively more harmful, foolish, and worthless compared to other emotional expressions. When we further explore beliefs about what can be accomplished by expressing anger at work, we find that promoting one's status isn't one of them. We discuss the theoretical and applied implications of these findings and point to new directions in the study of anger, power, and the workplace.